PALEOINTENSITY OF THE EARLY GEODYNAMO (2.45 GA) AS RECORDED IN KARELIA: A SINGLE-CRYSTAL APPROACH - Smirnov A.V.; Tarduno J.A.; Pisakin B.N. (My University, 2003)
We report Thellier paleointensity results from single plagioclase crystals derived from ca. 2.45 Ga border dikes of the Burakovka layered intrusion (Karelia, Russia). Rock magnetic and transmission electron microscope analyses indicate that these plagioclase crystals contain pseudosingle- to single-domain magnetite inclusions. Fifteen determinations from four dikes meet reliability criteria and yield an average paleointensity of 43.2 ± 10.8 muT, which corresponds to a virtual dipole moment of 8.43 ± 2.11 × 1022 Am2. Although our result is unlikely to adequately represent the time-averaged field, the mean and range of values are similar to those of the present-day field. These values suggest that the inner core, which may stabilize the geodynamo, had started to grow by Early Proterozoic time.
Keywords: Precambrian::Proterozoic; Докембрий::Протерозой